Enzymatic Incorporation of Emissive Pyrimidine Ribonucleotides - Srivatsan, Seergazhi G. (Chem Asian J, 2009)
The enzymatic incorporation of a series of emissive pyrimidine analogues into RNA oligonucleotides is explored. T7 RNA polymerase is challenged with accepting three non-natural, yet related, triphosphates as substrates and incorporating them into diverse RNA transcripts. The three ribonucloside triphosphates differ only in the modification of their uracil nucleus and include a thieno[3,2-d]pyrimidine nucleoside, a thieno[3,4-d]pyrimidine derivative, and a uridine containing a thiophene ring conjugated at its 5-position. All thiophene-containing uridine triphosphates (UTPs) get incorporated into RNA oligonucleotides at positions that are remote to the promoter, although the yields of the transcripts vary compared with the transcript obtained with only native triphosphates. Among the three derivatives, the 5-modified UTP is found to be the most “polymerase-friendly” and is well accommodated by T7 RNA polymerase. Although the fused thiophene analogues cannot be incorporated next to the promoter region, the 5-modified non-natural UTP gets incorporated near the promoter (albeit in relatively low yields) and even in multiple copies. Labeling experiments shed light on the mediocre incorporation of the fused analogues, suggesting the enzyme frequently pauses at the incorporation position. When incorporation does take place, the enzyme fails to elongate the modified oligonucleotide and yields aborted transcripts. Taken together, these results highlight the versatility and robustness, as well as the scope and limitation, of T7 RNA polymerase in accepting and incorporating reporter nucleotides into modified RNA transcripts.